The effect of problem based learning STEM (PBL STEM) on students' systems thinking skills on global warming material - Saputri, Syafah Anggriani; Suryadi, Ahmad (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2024)
This study explores the effect of PBL-STEM on students' systems thinking skills in global warming topics. This research is a quantitative study with a quasi-experimental design. This study was conducted in one of the public high schools in South Tangerang. The participants involved were 72 students. In the experimental class, students learned with PBL-STEM, and the control group used conventional learning. The system thinking instrument was developed using 24 tested multiple-choice questions with a reliability of 0.83. The results showed that PBL-STEM significantly affected students' systems thinking skills (p < 0.05). The experimental class students' systems thinking was higher than the control class' systems thinking. Furthermore, systems thinking skills in the experimental class increased, but the highest value was at level 1 with the essential difficulty; in the control class levels 1 and 2, there was a more significant increase. This study can be continued for future research investigating the effect of PBL STEM on systems thinking skills in different contexts.